Assessment of the quality of educational portals - R. G. Bolbakov; V. Y. Tsvetkov (Открытое образование (Москва))
The article describes the results of theoretical and experimental studies on the evaluation of the quality of educational information placed on information and educational portals. The methodology allows you to compare not only portals, but also the results of training on exam scores and test scores. The methodological basis of the assessment is the cognitive approach and the negentropic approach. The article gives a comparison of entropy and negentropy. On the basis of comparison, the authors propose a negentropic approach to assessing the quality of educational resources obtained as a result of information retrieval. The search results are evaluated by cognitive and perpetual scores. Estimates are introduced into the entropy formula and converted to the formula of negentropy. The negentropic approach serves as the basis for calculating the statistical amount of information obtained as a result of information retrieval. The cognitive approach serves as a basis for assessing the qualitative characteristics of educational information, such as: visibility, perceptibility, interpretability. Open information portalsare the source of educational resources. The article shows that modern information portals are often clogged with unreliable or unnecessary information, which makes it difficult to find relevant educational information. In contrast to the widespread methods for one relevanceassess of the information retrieval, this article differentiates the notion of the relevance of the information retrieval. The article introduces three qualitatively different notions of relevance: formal, semantic and perpetual – relevance. The article introduces new additional characteristics of the quality of information search, the coefficient of cognition and the coefficient of perpetuation. These coefficients are introduced into the formula for estimating entropy and obtain the cognitive-entropy formula. As a result, a new method for assessing the content of educational information was proposed, based on a new characteristic – cognitive-entropy. The cognitive entropy formula, unlike the entropy formula, allows us to estimate not a statistical amount of information, but a useful amount of information that satisfies the information need of the user. The article describes the results of a mass experiment involving students, bachelors and masters, including studies of a number of educational and public information portals. The number of requests to one portal exceeded 2500. This allowed us to obtain reliable statistical data for assessing the quality of the educational resources of the portal. The results of the experiment made it possible to classify portals according to their degree of suitability for obtaining educational resources. Limit cognitive entropy curves have been introduced, which can be regarded as analogues of the upper and lower boundaries in Shewhart charts, which are used in the theory of quality management. Shewhartchartsare used for a simple statistical evaluation of product quality. Limit cognitive entropy curves are used for qualitative and statistical evaluation of educational information on information portals. The method of estimating cognitive entropy is an author’s development. It allows you to estimate the amount of information not by the information volume, but by the quality of the necessary information, that satisfies the information requests of the user of educational resources. Based on the experiment, the portability or usability of portals for educational purposes were shown. If the results of calculating the conceptual curve of the portal lie below the lower limit curve of two, then such an educational portal is not suitable for educational purposes.